Proving the Element of Mens Rea in the Offence of Disseminating False and Misleading Information in Electronic Transactions: A Study of Tangerang District Court Decision Number 1240/Pid.Sus/2022/PN Tng - Antonius Maria Laot Kian; Rizky Pratama Putra Karo Karo; Niru Anita Sinaga; Ariy Khaerudin (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines how the subjective element of mens rea is regulated and proven in the Indonesian offence of disseminating false and misleading information in electronic transactions. Using normative legal research with statutory, case, historical, comparative, and conceptual approaches, it analyses Tangerang District Court Decision Number 1240/Pid.Sus/2022/PN Tng concerning Indra Kenz, compared with Bale Bandung District Court Decision Number 576/Pid.Sus/2022/PN Blb. The study finds that Indonesian regulation is dispersed and procedural, lacking technical standards for inferring intent from digital traces, and that the court constructed intent from consequences rather than from knowledge and volition. The findings recommend technical guidelines aligning electronic evidence authentication with algorithmic accountability.